STILISTIKA ALQURAN DALAM KISAH LUQMAN DAN IMPLIKASINYA TERHADAP CARA MENDIDIK ANAK - Agung Mulyadin (Lembaga P3M, 2022)
Abstract One way to pass the laws in the Holy Quran is by narrating the story, to be covered in a high form of language or sticism that results in imagination and fantasy. The selection of words also had a profound effect on the meaning that the account would want to explain. So that the Holy Quran has its own specialization of other stories. The study was intended to analyze the qur 'an in luqman's story, as well as to expose the child's educational patterns. Luqman's story contains several types of stilistics or figures of speech, as well as the correct selection of words in a whole sentence structure. Among the structure of the sentence in luqman's story is kalām khabarī, kalām insyāi, majāz mursal, isti’ārah, kināyah, taqdīm wa ta’khīr, uslūb tarhīm, syarat dan jawab syarat, shīgat mubālaghah. Then in the selection of the exact words yaizhu used before the word ya bunayya shows tenderness when to counsel. The level of sticism in luqman's account contains the ordinance of proper parenting. Between the attitudes and counsel that must be instilled upon children are to call their children by good names, teach a faith, do good to both parents, be grateful servants, follow the path of god and his prophet, be honest, order prayer, educate to do amar ma 'ruf nahyi munkar, be patient, and prohibit the act of insolence. Key words: stilistics, luqman, learn, child.